PENGARUH MEDIA PUZZLE TENTANG PENCEGAHAN COVID-19 DENGAN 5M TERHADAP PENGETAHUAN SISWA DI SDN KABANDUNGAN (Jurnal Kesehatan Siliwangi, 2023)
Background: Indonesia is a country with a high Covid-19 number. One of the cities in Indonesia that has the highest cases is Sukabumi City, totaling 10,503. Cikole district became the largest contributor, with 1,867 confirmed people. The village in this sub-district with high Covid-19 number is Selabatu, which is 366 cases, 5% of whom are aged 6-12 years. The high number of cases is influenced by a lack of knowledge about efforts to prevent Covid-19 with 5M. Health education is needed to increase knowledge, one of which is by using puzzle health promotion media, because in addition to education, it can be used as a play tool, thereby fostering high interest for elementary school students. Purpose: This study aims to analyze the effect of puzzle media on Covid-19 prevention with 5M on students knowledge at SDN Kabandungan. Methods: The study used a quasi-experimental method, with a one-group pretest-posttest design. The research subjects were 33 students, obtained by using total sampling technique. The instrument used to measure knowledge is a questionnaire, and analyzed using the Paired T-test. Results: The average difference between the results of the pretest and posttest was 12.13 with a r value= 0.000. Conclusion: The puzzle media has an effect on knowledge about preventing Covid-19 with 5M.